Bacteriological investigation of udder lobes of cows with mastitis slaughtered in the Elazi? region - Gülcü, Hasan Basri; Ertaş, Hasan Basri (My University, 2004)
Bacteriological examinations were performed on 206 mammary tissue samples taken from 160 cows with mastitis in Elazi?. The isolates were identified as Staphylococcus aureus (39.04%), Staphylococcus epidermidis (17.81%), Actinomyces pyogenes (14.38%), Escherichia coli (8.9%), Streptococcus agalactiae (6.16%), Streptococcus uberis (4.11%), Streptococcus dysgalactiae (3.42%), Corynebacterium bovis (1.37%), Pasteurella haemolytica (1.37%) and Bacillus cereus (1.37%).
Elazi? yöresinde mezbahada kesilen i?neklerde mastitisli meme loblarinin bakteriyolojik i?ncelenmesi
Keywords: Bacteria; Cow; Mastitis; Udder lobes